Structure and Properties of Multicomponent Tin Leaded Bronzes upon Die-Casting Depending on Pouring Temperature; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Korchmit A. V. Anton Viktorovich; Martyushev N. V. Nikita Vladimirovich; Tarasov S. Yu. Sergei Yulievich; Kvashnina O. S. Olga Sergeevna (Material Engineering and Technologies, 2015)
Title screen